Hierarchical Messaging Application for Android Using Salesforce (International Journal of Engineering and Computer Science, 2017)
Messaging applications are a dime a dozen nowadays and can only be differentiated on the basis of some unique features. These applications suffer from various limitations like free posting, joining, and lack of a hierarchy among other things when considered from an organizational or professional point of view. This paper presents the technology behind and structure of an application that limits the users in accordance with an organization specific hierarchy kept separate from the application to keep it universal so that this communication application would be professional and clutter-free. Users would be able to read relevant messages. Post if allowed, get update or news, and hale organizational events scheduled for them. These features would run on Android smartphones while other users would only be able to read the important messages via text SMS thus making the project available to all allowed, though in a limited capacity.